2013
DOI: 10.5229/jecst.2013.4.4.146
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based Bipolar Electrochemistry

Abstract: :We demonstrate that carbon electrodes screen-printed directly on cellulose paper can be employed to perform bipolar electrochemistry. In addition, an array of 18 screen-printed bipolar electrodes (BPEs) can be simultaneously controlled using a single pair of driving electrodes. The electrochemical state of the BPEs is read-out using electrogenerated chemiluminescence. These results are important because they demonstrate the feasibility of coupling bipolar electrochemistry to microfluidic paperbased analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 34 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…For example, cancer biomarkers have been detected on a closed indium-doped tin oxide (ITO) BE array biochip by parallel screening analysis with a simple visual ECL readout (209). Among the different analytical trends, paper-based bipolar ECL devices attracted great interest because they are versatile and inexpensive (213)(214)(215)(216)(217)(218)(219)(220). However, the paper-based bipolar systems exhibit usually a higher resistance than classic metallic electrodes, leading to a lower sensitivity.…”
Section: Optical Transductionmentioning
confidence: 99%
“…For example, cancer biomarkers have been detected on a closed indium-doped tin oxide (ITO) BE array biochip by parallel screening analysis with a simple visual ECL readout (209). Among the different analytical trends, paper-based bipolar ECL devices attracted great interest because they are versatile and inexpensive (213)(214)(215)(216)(217)(218)(219)(220). However, the paper-based bipolar systems exhibit usually a higher resistance than classic metallic electrodes, leading to a lower sensitivity.…”
Section: Optical Transductionmentioning
confidence: 99%
“…Also, the localization of the ECL reaction can be controlled in a 2-dimensional space on the perimeter of a square bipolar electrode by adjusting the electric field direction [30]. More recently, in an effort to limit the fabrication cost of BPE analytical platforms that are very often based on microfabrication techniques and incorporate expensive metal electrodes, paper-based devices were proposed [31,32].…”
Section: Open-configuration Ecl/bpementioning
confidence: 99%
“…Using a traditional screen-printing process, carbon-based electrodes can be printed directly onto cellulose paper to form electrochemical analytical devices. 107 By printing multiple designs on paper, Renault et al demonstrated the use of a single pair of driving electrodes to control 18 separate screen-printed bipolar electrodes. Each of these bipolar electrodes reads out the electrochemical state, demonstrating the multiplexing capabilities of screenprinted electrochemical microfluidic devices.…”
Section: Screen Printingmentioning
confidence: 99%